A Retrospective Study of the Impact of Rapid Diagnostic Testing on Time to Pathogen Identification and Antibiotic Use for Children with Positive Blood Cultures. Issue 4 (December 2016) - Veesenmeyer, Angela; Olson, Jared; Hersh, Adam; Stockmann, Chris; Korgenski, Kent; Thorell, Emily; Pavia, Andrew; Blaschke, Anne
Abstract Introduction Rapid identification of bloodstream pathogens provides crucial information that can improve the choice of antimicrobial therapy for children. Previous impact studies have primarily focused on adults. Our objective was to evaluate the impact of rapid testing in a children's hospital on time to organism identification and antibiotic use in the setting of an established antimicrobial stewardship program. Methods We conducted a retrospective study over three consecutive time periods (spanning January 2013–August 2015) as our hospital sequentially introduced two rapid testing methods for positive blood cultures. An antimicrobial stewardship program was active throughout the study. In the baseline period, no rapid diagnostic methods were routinely utilized. In the second period (PNAFISH), a fluorescent in situ hybridization test was implemented for gram-positive organisms and in the third a rapid multiplex PCR (rmPCR) test was employed. For children with positive blood cultures, time to organism identification use and duration of select antimicrobial therapies were compared between periods. Results Positive blood cultures were analyzed. Median overall time to organism identification was 23, 11, and 0 h in the baseline, PNAFISH, and rmPCR periods, respectively (p < 0.001 for both PNAFISH and rmPCR vs. baseline). For gram-negative organisms, only rmPCR performed significantly faster than baseline (p < 0.001). The duration of vancomycin use for coagulase-negative staphylococci was shorter in both the PNAFISH and rmPCR periods (mean 31 h in the baseline period, 12 and 14 h in the PNAFISH and rmPCR periods, respectively). For MSSA bacteremia, use of vancomycin was significantly decreased only in the rmPCR period (32% of patients vs. 64 and 72% in the baseline and PNAFISH periods; mean duration of 9 h vs. 30 and 26 h). There was no difference in use or duration of broad-spectrum gram-negative therapy across the three time periods. Conclusion Rapid diagnostic testing for children with positive blood cultures results in faster time to identification and can influence antibiotic prescribing in the setting of active antimicrobial stewardship particularly for gram-positive pathogens. Funding Merck.